ANALYSIS OF ADDITIONAL TAX CALCULATION AND REPORTING VALUE ADDED TAX (VAT) AND ITS IMPACT ON REPORT PRESENTATION FINANCE - Ashar, Muhammad; Azis, Muhammad; S, Masnawaty (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to determine whether the Value Added Tax (VAT) Calculation and Reporting is by the provisions of the applicable Tax Law and financial accounting standards and to analyze its effect on the Financial Reports at PT. Kalaborang Residence. The findings of this research are significant as they provide insights into the compliance of PT. Kalaborang Residence with the tax laws and financial accounting standards, and the practical implications of VAT on the company's financial statements. Kalaborang Residence. Samples and indicators are taken from the company's profit and loss report and balance sheet. The research method used in this research is the qualitative approach. Data was obtained from interviews, observations, and documentation related to the problems studied. The data obtained was then analyzed using interactive methods. Based on the research results of VAT Calculation and Reporting. PT Kalaborang Residence is by Law Number 42 of 2009 and Harmonization of Taxation Regulations Law Number 7 of 2021, using rates of 10% and 11% by calculating output tax minus input tax; there is no delay in depositing and reporting the company has used e-AnnualÂ Tax Returns so that you are not late in reporting every VAT periodâ€”the impact of Value Added Tax on the presentation of PT's financial statements. Kalaborang Residence has no impact because its End User is only an intermediary for its financial reports. If seen theoretically, PT. Kalaborang Residence, as a TaxableÂ Entrepreneur, is required to report its taxes in the financial reports contained in the Profit and Loss Report and Balance Sheet Report. From the results of observations made by researchers in the field during that period, there was no VAT that could not be credited to the PT's Profit and Loss Report.